The ability to correct an on-going action: Accuracy and correction time in elite fencing.übersetzter Titel (DE) - Zeuwts, L.; Koppo, K..; Cardon, G.; Lenoir, M. (Archives of Budo, 2017)
Background and Study Aim: Performing an attack in fencing takes fractions of a second implying that there is little time to correct an on-going movement to anticipate the opponent`s action. Studies in the lab evaluated correction times in artificial tasks but stand in shrill contrast to elite sports where via extensive training, motor programs are mastered and perfected. This study aim was knowledge about the capability of elite fencers to correct an on-going attack to a central target, when the target suddenly changes position at random time intervals.